MANAGEMENT EDUCATION IN THE CONTEXT OF SOCIAL AND PEDAGOGICAL TRANSFORMATIONS - Кондур, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
Educational and upbringing, pedagogical-psychological susprisingly theory, its models and concepts seek to redefine private and the public mind. Based on these grounds, in the future, it allows of education to develop to develop a more inclusive philosophical vision of education, to apply directly to the problems of democratization and changes in social relations in the direction of equality and social justice in the field of education. Examines trends in educational institutions and models of globalizing society in the context of our particular relationship of education and society, man and the state, and processes. Ongoing research and systems analysis of neoliberal reforms on the level of society in general and education in particular. Examines substantive, structural and functional characteristics of the concept of education in the context of institutional tendencies of social life, as well as forms and possibilities of its methodological application. Consider a model of education, as embodied in the programs of social development and learning, which are primarily designed to teach people how to lead an independent and original research themselves, society and knowledge systems. However, it is proved that the models and programs should not be cut off from any individual and the collective system of moral and social values, theoretical and applied training, nor from further use of the acquired values, norms and skills in everyday life, science, or in production, sphere of all social institutions. Point of view of social and educational, pedagogical-psychological, normative understanding and social critics also requires the use of active efforts in the reconstruction of education and society, the social vision of what education and human life can be and what their specific limitations in existing societies.